Analisa Usaha Yayasan Mengimplementasikan Akuntansi - Ade Palupi (Wahana Riset Akuntansi, 2022)
The study analyzed how the foundation strives and struggles to apply accounting in accordance with standards so that it can properly compile financial statements. The purpose of this research is to improve the nonprofit accounting literature and assist the foundation in accelerating its capabilities in the field of accounting. This study applies case studies as a research method to construct by using Bourdieu's theory of practice as a theoretical framework. Data is obtained from documentation and interviews from two foundations as case studies. The results of this research it believes that the foundation's accounting pratice in Indonesia is an accounting field. The field forces the yayasan to keep fighting and compete in acquiring the types of capital such as economic, cultural and social to execute accounting practices. This research finds that social capital is the capital most relied upon by foundations in order to master accounting skills. In addition, the habitus agent of change of the foundation plays an important role in the implementation of accounting in the foundation.  Accounting can be classified as symbolic power because it forces the foundation to comply through legislation and regulations legitimized by the government. On the other hand, the Foundation has stakes of amanah and professional values in maintaining its position in front of the general public. Keywords: Nonprofit Accounting, Foundation Accounting, Foundation, Bourdieu